Long Covid Incidence and Influencing Factors of Covid-19 Survivors in the Working Area of Lubuk Begalung Health Center, Padang - Khairsyaf, Oea; Masrul Basyar; R.A Ananda Nuriman; Khairudin Hamdani; Hadya Gorga (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Corona Virus Disease 2019 (COVID-19) is an acute respiratory infection caused by the Severe Acute Respiratory Syndrome-Corona Virus-2 (SARS-CoV-2). Clinical symptoms depending on the clinical severity of the patient which consists of mild, moderate, severe and critical. In COVID-19 patients who recover, pulmonary fibrosis can occur, which can lead to impaired lung function. In addition, there are also long covid complaints such as shortness of breath, nausea, coughing. Methods. The research design is an observational study. The study was conducted at the Lubuk Begalung Padang Health Center from January 2021 to March 2021. The study population was all mild, moderate to severe COVID-19 patients in the working area of the Lubuk Begalung Padang Health Center and experienced long covid symptoms. Results. The average age of COVID-19 survivors in this study was 46 years with a higher prevalence of women than men. The results of the pulmonary vap examination of most of the respondents were within normal limits. The most common distribution of clinical severity in this study was mild. The most common symptoms of long covid are weakness and muscle aches. Conclusion. No correlation was found between the clinical complaints of survivors with the clinical severity and lung function.